2016
DOI: 10.1016/j.metabol.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and diabetes

Abstract: Non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2DM) are common conditions that regularly co-exist and can act synergistically to drive adverse outcomes. The presence of both NAFLD and T2DM increases the likelihood of the development of complications of diabetes (including both macro- and micro- vascular complications) as well as augmenting the risk of more severe NAFLD, including cirrhosis, hepatocellular carcinoma and death.The mainstay of NAFLD management is currently to reduce modifiable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
392
3
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(414 citation statements)
references
References 132 publications
8
392
3
11
Order By: Relevance
“…NAFLD comprises a complex spectrum of disease that begins with liver fat accumulation (non alcoholic fatty liver or NAFL) and progress with inflammation and fibrosis (non alcoholic steatohepatitis or NASH). There is now a wealth of evidence that NAFLD increases risk of type 2 diabetes (summarised in [1,4]) but there is limited evidence to date that treatment of NAFLD decreases risk of T2DM. We have shown previously that resolution of fatty liver (detected by ultrasound) over 5 years, was independently associated with marked attenuation of the risk of incident T2DM [5] and also incident hypertension [6], over five years of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD comprises a complex spectrum of disease that begins with liver fat accumulation (non alcoholic fatty liver or NAFL) and progress with inflammation and fibrosis (non alcoholic steatohepatitis or NASH). There is now a wealth of evidence that NAFLD increases risk of type 2 diabetes (summarised in [1,4]) but there is limited evidence to date that treatment of NAFLD decreases risk of T2DM. We have shown previously that resolution of fatty liver (detected by ultrasound) over 5 years, was independently associated with marked attenuation of the risk of incident T2DM [5] and also incident hypertension [6], over five years of follow up.…”
Section: Introductionmentioning
confidence: 99%
“…The NAFLD imposes the risk for the diabetes and its complications, in turn, diabetes makes an individual more likely to have more severe NAFLD with the associative complications of cirrhosis and mortality. 48
10.1080/19336918.2017.1379634-f0002Figure 2.The involvement of the VEGF-B in the lipids translation, and the observed phenotype in the targeted VEGF-B treatment in various rodent animals. The black line stands for the pathways under physical conditions; the red for the pathological conditions; the green for the changes after the neutralizing VEGF-B strategies (the VEGF-B −/− model or VEGF-B antibody treatment).
…”
Section: Introductionmentioning
confidence: 99%
“…The NAFLD imposes the risk for the diabetes and its complications, in turn, diabetes makes an individual more likely to have more severe NAFLD with the associative complications of cirrhosis and mortality. 48 …”
Section: Introductionmentioning
confidence: 99%
“…However, whether DM increases the risk of developing NAFLD was not clear. 40 In a large series of 432 patients, the coexistence of DM with NAFLD was found to be an independent risk factor for fibrosis. 41 The prevalence of NAFLD among DM patients varies with the method of diagnosis and the population studied; some studies have shown that NAFLD may be present in up to 70 per cent of patients with DM.…”
mentioning
confidence: 99%